An In Vitro Model for Fibroblast Photoaging Comparing Single and Repeated UVA Irradiations. (25th July 2017) - Nakyai, Wongnapa; Saraphanchotiwitthaya, Aurasorn; Viennet, Céline; Humbert, Philippe; Viyoch, Jarupa
Abstract: The current method for efficient evaluation of antiphotoaging compounds is an in vitro skin culture model using a single ultraviolet A (UVA) irradiation of fibroblasts. However, skin photoaging is caused by repeated exposure to UVA radiation. The objective of this study was to develop an appropriate model for in vitro skin photoaging by comparing the different effects of single (5 J cm −2 ) and repeated exposures (5 J cm −2 × 3 times) of fibroblasts to UVA irradiation. Our results demonstrated that a single and repeated exposure to UVA irradiation had different effects on fibroblasts. In the single UVA‐irradiated group, collagen lattice contraction and the protein levels of type I procollagen and matrix metalloproteinase‐1 (MMP‐1) increased, while the levels of fibronectin and alpha‐smooth muscle actin ( α ‐SMA) were unchanged, compared to levels in the non‐UVA‐irradiated group (control). In contrast, repeated UVA exposure significantly induced G0/G1 cell cycle arrest, reduced collagen lattice contraction and type I procollagen and fibronectin expression, and increased MMP‐1 expression. There was no difference in α ‐SMA expression when comparing repeatedly irradiated and non‐UVA‐irradiated fibroblasts. Our findings clearly indicate that repeated UVA irradiation of cells induces malfunctions found in photoaged skin and is an appropriate in vitro skin model of photoaging. Abstract : The different effects between single and repeated exposure of fibroblasts to UVA (5 J cm −2 ) radiation on the expressions of proteins and the contractile capacity were determined. The single dose of UVA radiation remakably increased expressions of type I procollagen and MMP‐1 of fibroblasts. Moreover, the contractile capacity, measured by collagen lattice retarction, of single UVA‐irradiated fibroblast was found. On the other hand, repeated UVA irradiation reduced expressions of type I procollagen and fibronectin, while increased expression of MMP‐1 of fibroblasts. The contractile capacity of repeated UVA‐irradiated fibroblasts also reduced. Therefore, repeated UVA‐irradiated fibroblasts exhibited malfunctions as found in photoaged skin.